Stress level of physical education students: How to do the learning during the covid-19 pandemic? - Mylsidayu, Apta (Journal Sport Area, 2021)
Many physical education students complain that online lectures are unsatisfactory because they do not practice directly (only theory). Students feel not really understand the material presented because study with offline and online is different, and lecture assignments are piling up so that causing physical education students to become boredom and stressed. This study aims to determine the level stress of college students during the COVID-19 pandemic. Quantitative descriptive is the method used in this research, with a total sample of 168 student used accidental sampling techniques. Measurement the level of stress is using The Kessler Psychological Distresss Scale (K10) which is distributed via Google form. Data analysis used is quantitative description analysis techniques with percentages. The results show that the stress level of physical education students is in the heavy category of 34% (58 people). So, students can manage stress by stress coping, managing stress, doing physical activity, thinking positively, and doing self-talk